Student Language Anxiety and Their English Achievement - Sandalapu, Yogus; Dompas, Yvonne G. (International Journal of Education, Information Technology, and Others, 2024)
This study was aimed to reveal the significant correlation of language learners’ anxiety toward their achievement in English. Anxiety is one of the major affective factors in learning a language. This investigation answers these following questions: 1) What is the extend of English Anxiety of students? 2) What is the extend of achievement in English of students? 3) Is there significant difference in anxiety and achievement in English when classified according to 3.1 Sex, 3.2 Major? 4) Is there significant relationship between students’ anxiety and achievement in English? This enquiry utilized descriptive correlation design with convenience sampling with 30 respondents of Toraja View Academy who voluntarily answered the validated questionnaires through Foreign Language Classroom Anxiety Scale (FLCAS) adopted from Horwitz, Horwitz, and Cope (1986). The result shows that there is no significant correlation between students’ language anxiety and their English achievement as the descriptive statistic result shown. The level of language learner’s anxiety is moderate meanwhile their English achievement is average. Besides, that there is no significant difference of learner’s anxiety based on their sex and major.